1964
DOI: 10.1302/0301-620x.46b4.726
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve Lipoma in the Hand

Abstract: 1. Two cases are reported in which there was diffuse fibro-fatty overgrowth or tumour formation involving the adipose tissue of the median nerve. In each the diagnosis was confirmed by operation and histological examination. 2. The first case is an example of the developmental abnormality usually referred to as "macrodystrophia lipomatosa." The second case should be termed fibrolipoma. 3. The literature is reviewed; no case of fibrolipoma has been recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 7 publications
0
20
1
1
Order By: Relevance
“…In 2008, Baena-Ocampo LC et al, reported tendon sheath lipoma which was associated with quadriceps tendon rupture [7]. Campbell, in 1954, reported a lipoma producing lesion in the deep branch of the radial nerve, which was detected by applying pressure only [8].…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Baena-Ocampo LC et al, reported tendon sheath lipoma which was associated with quadriceps tendon rupture [7]. Campbell, in 1954, reported a lipoma producing lesion in the deep branch of the radial nerve, which was detected by applying pressure only [8].…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of these tumors arise exclusively in the median nerve [2][3][4][5]. However, involvement of the ulnar nerve [2,4], radial nerve [6,7], and dorsum of the foot [2] also has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrolipomatous hamartoma has been termed fibrofatty overgrowth, lipomatous hamartoma, lipofibmoma, lipofibmomatous hamartoma, and fatty infiltration of the median nerve [3,7]. It occurs most often in infants, and less commonly in children and young adults [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known as a fibrofatty overgrowth, fibrolipomatous hamartoma, intraneural lipoma, and lipomatous hamartoma [1,2] . This lesion is usually unilateral and has no known genetic component.…”
Section: Introductionmentioning
confidence: 99%